KAJIAN KADAR AIR TERHADAP UMUR SIMPAN SIMPLISIA NABATI MINUMAN FUNGSIONAL WEDANG REMPAH - Maria Ulfah; Wawan Priyanto; Heri Prabowo (Bajang Institute, 2022)
Abstract: Indonesian generally use spices as a mixture of beverages ingredients. Along with the increasing public demand for spices, it is necessary to make a products diversification, one of which is instant/dipped spice functional beverages (Wedang). Wedang Rempah instant / dip is an instant beverages made from spices native to Indonesia. Wedang Rempah Mbah Kung develops spice-based instant beverages. Wedang spices ingredients used in Wedang Rempah Mbah Kung include ginger, turmeric, lemongrass, cardamom, star anise, temulawak, cinnamon, sappan wood, cloves, dahl, root of reeds, tamarind, purwoceng, lime and so on. This research was aimed to determine the effect of simplicia water content on the enzymatic process of the functional beverages Wedang Rempah Mbah Kung. The method of determining the water content of simplicia using the Gravimetric method and analyzed by qualitative descriptive. Wedang Rempah Slim, Wedang Rempah Bugar, Wedang Rempah Ceria Anak Sehat, Wedang Rempah Purwoceng, Wedang Rempah Rosela have a water content of 8.26%, 10.34%, 7.72%, 10.12%, 8.59%. The water content of simplicia should be less than 10%. If the water content is greater than 10%, it will cause enzymatic processes and damage by microbes. From the results of the research, it can be concluded that the simplicia water content of some processed Wedang Rembah Mbah Kung, for products Wedang Renpah Slim, Wedang Rempah Ceria Anak Sehat, Wedang Rempah Rosela has a water content of less than 10% so that the enzymatic process takes place slowly when compared to Wedang Rempah Bugar and Wedang Rempah Purwoceng have simplicia water content of more than 10%.